Pod set and Pollen Viability Studies in Yard Long Bean (Vigna unguiculata sub sp. sesquipedalis) - Merin E G (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2019)
A study was conducted in a yard long bean (Vigna unguiculata sup/ssp. sesquipedalis) hybrid VS 50 (Kakkamoola Local) x VS 26 (Vellayani Jyothika) to assess the percentage fruit set at two time intervals and to identify the best time interval for pollination in yard long bean hybrids. Hand pollination was done using VS 50 as female parent and VS 26 as male parent for seven consecutive days at two time intervals, 6.30 – 7.30 am and 7.30 – 8.30 am. Higher percentage of fruit set (36.8 %) was observed between 6:30 – 7:30 a.m. as compared to the time interval 7:30 – 8:30 am. (23.8%). Pollen viability was determined for the parents VS 50 (Kakkamoola Local) and VS 26 (Vellayani Jyothika) at 6.30, 7.30 and 8.30 am. Highest pollen viability for both the parents VS 50 and VS 26 was observed during 7.30 am. The present study shows that the best time interval for crossing in yard long bean is 6.30- 7.30 a.m.